Analisis Kualitas Udara Ambien di Area Industri Semen PT X Desa Wajok Hulu Berdasarkan Indeks Standar Pencemar Udara (ISPU) - Widya Ningrum Palureng, Rurika; Nurul Khalik, Ikhdam (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2025)
The cement industry plays a significant role in contributing to air pollution, primarily due to combustion and raw material processing that release particulate matter and gaseous pollutants. This research aims to evaluate the ambient air quality around the PT X cement plant in Wajok Hulu Village, Mempawah Regency, and to assess the air pollution level based on the Air Pollutant Standard Index (ISPU) in accordance with Regulation of the Minister of Environment and Forestry No. 14 of 2020. Measurements were conducted at two sampling points, production area and entrance area, with parameters including PM₁₀, PM₂.₅, SO₂, NO₂, CO, O₃, and HC. Air samples were collected using a High Volume Air Sampler (HVAS) and impinger for 24 hours, and the results were compared with the National Ambient Air Quality Standards as stipulated in Government Regulation No. 22 of 2021. The findings indicate that all parameters were below the permissible limits, with ISPU values under 50, categorized as “Good” air quality. The highest ISPU values were recorded for SO₂ and particulate matter (PM₁₀ and PM₂.₅), which are typical emissions from fuel combustion and cement raw material processing. These results suggest that the emission control systems at PT X are operating effectively; however, regular monitoring is necessary to maintain air quality stability. The study emphasizes the importance of implementing emission control technologies such as dust collectors, electrostatic precipitators, and green buffer zones around the plant area as mitigation strategies toward sustainable cement industry practices.